Structural Optimization of Berberine as a Synergist to Restore Antifungal Activity of Fluconazole against Drug‐Resistant Candida albicans. Issue 1 (4th November 2013) - Liu, Hong; Wang, Liang; Li, Yan; Liu, Jiang; An, Maomao; Zhu, Shaolong; Cao, Yongbing; Jiang, Zhihui; Zhao, Mingzhu; Cai, Zhan; Dai, Li; Ni, Tingjunhong; et al.
Abstract We have conducted systematic structural modification, deconstruction, and reconstruction of the berberine core with the aim of lowering its cytotoxicity, investigating its pharmacophore, and ultimately, seeking novel synergistic agents to restore the effectiveness of fluconazole against fluconazole‐resistant Candida albicans. A structure–activity relationship study of 95 analogues led us to identify the novel scaffold of N‐(2‐(benzo[d][1, 3]dioxol‐5‐yl)ethyl)‐2‐(substituted phenyl)acetamides 7 a–l, which exhibited remarkable levels of in vitro synergistic antifungal activity. Compound 7 d (N‐(2‐(benzo[d][1, 3]dioxol‐5‐yl)ethyl)‐2‐(2‐fluorophenyl)acetamide) significantly decreased the MIC80 values of fluconazole from 128.0 μg mL−1 to 0.5 μg mL−1 against fluconazole‐resistant C. albicans and exhibited much lower levels of cytotoxicity than berberine toward human umbilical vein endothelial cells.